Efficiency of calcined kaolin and silica fume as cement replacement material for strength performance - Wong, H.S.; Razak, H.A. (2005)
The concept of efficiency can be used for comparing the relative performance of various pozzolans when incorporated into concrete. In this paper, an alternative approach for the evaluation of efficiency factor k of a pozzolanic material has been introduced. The method, developed following Abram's strength-W/C ratio rule, calculates efficiency in terms of relative strength and cementitious materials content. The advantage of this method is that only two mixtures are required to determine the k factor of a specific mixture. A laboratory investigation on silica fume (SF) and metakaolin (MK) concrete found that the computed efficiency factors varied with pozzolan type, replacement level and age. At 28 days, the k values ranged from 1.6 to 2.3 for MK and 2.1 to 3.1 for SF mixtures, while at 180 days, the k values varied from 1.8 to 4.0 for MK and 2.4 to 3.3 for SF mixtures. Generally, the k factors increased with age but declined with higher pozzolanic content. It was also observed that change in W/CM ratio from 0.33 to 0.27 did not significantly affect the resultant efficiency factors.